Extension of the GSMW Formula in Weaker Assumptions - Wenfeng Wang; Xi Chen (Abstract and Applied Analysis)
In this note, the generalized Sherman-Morrison-Woodbury (for short GSMW) formula (A+YGZ∗)⊙=A⊙−A⊙Y(G⊙+Z∗A⊙Y)⊙Z∗A⊙ is extended under some assumptions weaker than those used by Duan, 2013.